Differential Effects of Fkbp4 and Fkbp5 on Regulation of the Proopiomelanocortin Gene in Murine AtT-20 Corticotroph Cells - Kageyama, Kazunori (Int J Mol Sci, 2021)
The hypothalamic-pituitary-adrenal axis is stimulated in response to stress. When activated, it is suppressed by the negative feedback effect of glucocorticoids. Glucocorticoids directly inhibit proopiomelanocortin (Pomc) gene expression in the pituitary. Glucocorticoid signaling is mediated via glucocorticoid receptors, 11β-hydroxysteroid dehydrogenases, and the FK506-binding immunophilins, Fkbp4 and Fkbp5. Fkbp4 and Fkbp5 differentially regulate dynein interaction and nuclear translocation of the glucocorticoid receptor, resulting in modulation of the glucocorticoid action. Here, we explored the regulation of Fkbp4 and Fkbp5 genes and their proteins with dexamethasone, a major synthetic glucocorticoid drug, in murine AtT-20 corticotroph cells. To elucidate further roles of Fkbp4 and Fkbp5, we examined their effects on Pomc mRNA levels in corticotroph cells. Dexamethasone decreased Pomc mRNA levels as well as Fkpb4 mRNA levels in mouse corticotroph cells. Dexamethasone tended to decrease Fkbp4 protein levels, while it increased Fkpb5 mRNA and its protein levels. The dexamethasone-induced decreases in Pomc mRNA levels were partially canceled by Fkbp4 knockdown. Alternatively, Pomc mRNA levels were further decreased by Fkbp5 knockdown. Thus, Fkbp4 contributes to the negative feedback of glucocorticoids, and Fkbp5 reduces the efficiency of the glucocorticoid effect on Pomc gene expression in pituitary corticotroph cells.